Feasibility of Clinical Dietetics E-Module to Improve Learning Achievement of Vocational Students - Rahmatunisa, Nadya; Sofyan, Herminarto; Daryono, Rihab Wit; Nurtanto, Muhammad (Journal of Education Technology, 2022)
The unavailability of interactive media, namely e-module, has an impact on students so that they tend to be passive and less interested in learning in clinical dietetics subjects, resulting in student learning outcomes that are not by competency standards. This study aims to develop and prove the feasibility of e-modules in nutrition science and explore the importance of developing e-modules to improve learning achievement. This study is a Research and Development (R&D) using a 4-D model with a quantitative approach. The subjects of this study were students of class X majoring in culinary, which amounted to 124 respondents. The data collection technique used interviews and questionnaires that were used to validate and prove the results of the e-module feasibility. The results of material expert validation show that the e-module is very feasible to use with a percentage of 91.250%, media experts contribute to media eligibility 91.875%, while student assessments get 86.618% eligibility. So that the clinical dietetics e-module is feasible to be used as learning. Parametric statistics with comparative analysis of two samples using the T-test, Dunnet-C, and Tukey's test were conducted to determine differences in the variables of gender, age, and class. Comparative analysis proves that there is no significant difference between class X students in assessing the development of nutrition science e-modules. The existence of a clinical dietetics e-module can make it easier for students to learn and carry out learning independently so that student learning outcomes are according to competence.